[Ilocos ; Sir, servicen ; Rage band [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
Takes a look at Ilocos Norte two years later, the EDSA revolution ; a look at juvenile prostitution that takes place in Pagsanjan Laguna ; an interview with Rage Band.